Analysing Technological Pedagogical and Content Knowledge (TPACK) of Pre-Service Science Teachers - Novi Ratna Dewi; Ani Rusilowati; Sigit Saptono; Sri Haryani; Prasetyo Listiaji (International Conference on Science, Education, and Technology, 2021)
In 21st century learning, it is important for science teachers to have good knowledge in integrating technology into learning which is known as the Technological Pedagogical Content Knowledge (TPACK) framework. This study aims to analyze the TPACK of pre-service science teachers. The method used was quantitative research with surveys. The research subjects were students at Science Education Study Program, Universitas Negeri Semarang as pre-service science teachers. The instrument was developed based on the aspects of PK, CK, TK, PCK, TPK, TCK, and TPCK. The results showed that overall the pre-service science teacher TPACK obtained quite good criteria, then if it was categorized the results were 14.75% less good, 70.43% quite good, and 14.75% good. This research can be a reference in the development and improvement of TPACK for future pre-service science teachers.